Óleo de soja, pré e pós processamento de rações para tilápia do Nilo (Oreochromis niloticus) - Moreira, Pedro Oliveira (2014)
The aim of this study was to evaluate the influence of different application forms of soybean oil in diets for Nile tilapia. We used 192 fish with average weight of 15,34 ± 0,6 g and total length of 8,61 ± 2,11 cm in a completely randomized design with four treatments and four replicates. The animals were fed for a period of 61 days with diets containing the same inclusion level of soybean oil (3%) in three application forms: oil after extrusion, oil before extrusion, oil before (50%) and after (50%) extrusion and one control diet without soybean oil. We evaluated the performance parameters, filet chemical composition and blood biochemistry. The data were submitted to homogeneity and normality test, analysis of variance (ANOVA) and Tukey’s test at 5% of significance. There were no significant difference (P>0.05) for the parameters of performance, chemical composition and blood biochemistry among the three different forms of soybean oil application. However, the control diet showed the lowest values (P<0.05) of performance and triglycerides in relation to the diets with soybean oil regardless of its aplication. The use of soybean oil concomitant to a source of carbohydrate provided better performance of the animals. The different application forms of soybean oil, for Nile tilapia juveniles, not interfere in the analyzed variables.